Phytochemical Analysis, Anti-Inflammatory, and Antioxidant Activity of Selected Medicinal Plants in Mandiangin Rainforest in South Kalimantan, Indonesia: Medicinal Plants in Mandiangin Rainforest in South Kalimantan - Yusanto Nugroho; Windy Budianto; Salmon Siahaan; Purwakaning Agung; Iskandar Thalib; Eko Suhartono (Journal of Tropical Life Science, 2023)
Mandiangin is one of the tropical rainforests in South Kalimantan, with highly diverse plants used for health and medicinal purposes. To date, scientific evidence on these plants' content and bioactivities remain lacking for further medical applications. In this perspective, this study aimed to determine the phytochemical contents of six selected plants, which include the Bilaran Kusan (Passiflora foetida), Sembilakan (Caesalpinia sp), Bamban Batu (Donax cenniformis), Kilayu (Aglaia sp), Ulur-Ulur (Tetrastigma sp), and Mali-Mali (Leea indica) from the Mandiangin rainforest, in addition to their antioxidant and anti-inflammatory activity. Results revealed that the Leea indica extracts exhibited the highest flavonoid content (70.892 ± 0.34 mg/ml QE), while the highest tannin (2.101 ± 0.02 mg/ml GAE) and alkaloid contents (25.30 ± 0.71 %) were recorded for the Aglaia sp species. Meanwhile, Passiflora foetida showed the highest saponin content at (31.78 ± 2.97 %). Based on the study findings, the extracts of all six plants from the Mandiangin rainforest possessed medically valuable phytochemical constituents, as seen from their appreciable antioxidant and anti-inflammatory activity. Of all these plants, P. foetida and L. indica demonstrated the highest antioxidant activity, whereas the highest anti-inflammatory activity was noted for the P. foetida, Aglaia- and Caesalpinia species.